ecoinvent – An Introduction to the LCI Database and the Organization Behind it - Lucia, VALSASINA; Emilia, MORENO-RUIZ; Carl, VADENBO; Avraam, SYMEONIDIS (日本LCA学会誌, 2023)
The year 2023 marks both the tenth anniversary of the ecoinvent association and twenty years since the first release of the ecoinvent life cycle inventory （LCI） database. In this article, we reflect on the achievements of ecoinvent and its LCI database to date, introduce its main features and application areas, and invite the LCA community in Japan and more broadly to engage and benefit from the resources and support provided. Through continuous development and updates, the ecoinvent database has evolved into a valuable resource for LCA practitioners worldwide, offering reliable, transparent, and consistent background data to support sustainable decision-making and environmental assessments. Looking forward ecoinvent plans to enhance its data framework, collaborate with global data providers, improve user-friendliness, facilitate data exchange, and support future extensions to advance sustainable decision-making worldwide.